Impact of policy measures on wheat-to-bread supply chain during the global commodity price peaks: The case of Serbia - Ivan Djuric (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
The aim of this study is to analyze the impact of governmental market interventions in Serbia, among them a wheat export ban, on the country's integration into the international wheat market and the domestic wheat-to-bread supply chain during the global commodity price peaks in 2007/08 and 2010/11. By applying two regime-dependent price transmission models (i.e. Markov-switching models), we help to clarify the impact of the governmental market interventions on two different price transmission contexts: the horizontal one, where we analyze the price transmission and market integration between the Serbian and the world wheat markets; and the vertical one, where we analyze the price transmission mechanisms within the Serbian wheat-to-bread supply chain. Furthermore, we conducted simulations of flour and bread production costs and the bakers' and retailers' profits in order to identify who benefited from and who lost due to the extensive governmental interventions. [... ] – – Das Ziel dieser Studie ist es, die Auswirkungen der Marktinterventionen der serbischen Regierung während der Agrarpreisspitzen 2007/8 und 2010/11, darunter ein Weizenexportverbot, auf die serbische internationale Weizenmarktintegration und die heimische Weizen-Brot-Wertschöpfungskette zu analysieren. Durch die Anwendung zweier regime-dependenter Preistransmissionsmodelle (z.B. Markov- Modelle), helfen wir, die Auswirkungen der Marktinterventionen auf zwei verschiedene Preistransmissionskontexte zu verstehen: Den horizontalen, wo wir die Preistransmission und die Marktintegration zwischen dem serbischen und den globalen Weizenmärkten untersuchen, und die vertikale Preistransmission, wo wir die Preistransmissionsmechanismen innerhalb der serbischen Weizen-Brot- Wertschöpfungskette analysieren. Darüber hinaus unternehmen wir Simulationen der Produktionskosten von Mehl und Brot sowie der Gewinne der Bäcker und Einzelhändler, um zu identifizieren, wer von den extensiven politischen Interventionen profitierte und wer darunter litt. [...]
urn:nbn:de:gbv:3:2-37542
Keywords: 330